Hubungan Karakteristik Remaja Dengan Tingkat Kecanduan Gadget di Kota Bukittinggi - Febrina, Cory; Mariyana, Rina (Universitas Fort De Kock Bukittinggi, 2020)
Background: Heavy addiction to gadgets has a biological and psychological impact. According to the Indonesian Internet Service Providers Association (APJII) the prevalence of adolescents playing online games is 44.10% and in adolescents aged 10 to 24 years approximately 18.40% in the year 2016. In 2020 the results of research in the city of Bukittinggi showed 75% of adolescents used gadgets to play games. The purpose of this study was to determine the relationship between children's characteristics and the level of gadget addiction. Method: Research method This research is descriptive analytic using cross sectional approach. The study population was adolescents in the city of Bukittinggi. The sample technique is stratified random sampling of 130 people. Data collection used a questionnaire. Data were analyzed univariately and bivariately using the chi_square test and nonparametric correlation. Result: The results and discussion showed that there was a significant relationship between the duration of waking up and the use of gadgets on the level of gadget addiction in adolescents with results (P value 0.013). There is no significant relationship between age and the level of gadget addiction with value (P value = 0.323). There is no significant relationship between gender and the level of gadget addiction (P value = 0.579). Conclusions: It needs continuous efforts from public health nurses, involving cross-sectoral education for schools and families related to gadget addiction.Keywords: Characteristics, Gadget Addiction, Adolescents